3-Substituted pyrazoles and 4-substituted triazoles as inhibitors of human 15-lipoxygenase-1. Issue 15 (1st August 2015) - Pelcman, Benjamin; Sanin, Andrei; Nilsson, Peter; No, Kiyo; Schaal, Wesley; Öhrman, Sara; Krog-Jensen, Christian; Forsell, Pontus; Hallberg, Anders; Larhed, Mats; Boesen, Thomas; Kromann, Hasse; et al.
Graphical abstract: Abstract: Investigation of 1 N -substituted pyrazole-3-carboxanilides as 15-lipoxygenase-1 (15-LOX-1) inhibitors demonstrated that the 1 N -substituent was not essential for activity or selectivity. Additional halogen substituents on the pyrazole ring, however, increased activity. Further development led to triazole-4-carboxanilides and 2-(3-pyrazolyl) benzoxazoles, which are potent and selective 15-LOX-1 inhibitors.